The Contribution of Corporate Social Responsibility (CSR) Practices to the Breaking of the Glass Ceiling: The Case of Moroccan Enterprises - Taoufik AIT BOUCHGOUR; Tayeb BIAD; Moulay Sadik MALIKI; Khalid LAHYANI (Communications of International Proceedings, 2021)
Morocco has deployed great efforts to support and encourage gender equality through adhering to various national and international legal instruments. It seems, however, that these measures have not had any sufficient impact on women’s current situation in the job market. Research conducted by the Financité Institute shows that none of the companies listed on the Casablanca Stock Exchange is directed by a woman. The research also reveals that women account for less than 12% of a board of directors. Women’s difficulty to reach and hold high positions is clearly illustrated by the phenomenon of glass ceiling that hinders women’s career and leads to their rarity at the top of companies’ hierarchy. The present article is concerned with the policies that Moroccan companies can implement, within the framework of the CSR approach, so that they can promote women’s progress and break the glass ceiling. It presents a case study of a Moroccan industrial company that was selected as among the top CSR performers. It also tries to highlight all the practices that this company has developed in terms of professional equality and their effectiveness in the breaking of the glass ceiling.
Keywords: Diversity management; Gender; Glass Ceiling; CSR.